CD96 (TACTILE), CD226 (DNAM-1) and TIGIT in the regulation of immune functions in chronic myeloid leukemia - Carvalho, Adriana Marques (2017)
Dissertação de Mestrado em Bioquímica apresentada à Faculdade de Ciências e Tecnologia